2012
DOI: 10.1098/rstb.2011.0359
|View full text |Cite
|
Sign up to set email alerts
|

Multistability in auditory stream segregation: a predictive coding view

Abstract: Auditory stream segregation involves linking temporally separate acoustic events into one or more coherent sequences. For any non-trivial sequence of sounds, many alternative descriptions can be formed, only one or very few of which emerge in awareness at any time. Evidence from studies showing bi-/multistability in auditory streaming suggest that some, perhaps many of the alternative descriptions are represented in the brain in parallel and that they continuously vie for conscious perception. Here, based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
108
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 68 publications
15
108
1
Order By: Relevance
“…The precise mechanism by which predictability acts upon auditory scene analysis is still unclear. One interpretation that is consistent with the available evidence suggests that detecting the presence of a predictable pattern stabilizes the corresponding auditory stream by increasing the perceptual coherence of its elements, thus making this stream easier to maintain for longer periods of time [5,17,18,30]. If this interpretation is correct, then the same mechanism should apply when the listener perceives only one stream -in other words, predictable patterns should stabilize an integrated percept when compared to an arrangement of similar tones with randomly jittered feature values.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…The precise mechanism by which predictability acts upon auditory scene analysis is still unclear. One interpretation that is consistent with the available evidence suggests that detecting the presence of a predictable pattern stabilizes the corresponding auditory stream by increasing the perceptual coherence of its elements, thus making this stream easier to maintain for longer periods of time [5,17,18,30]. If this interpretation is correct, then the same mechanism should apply when the listener perceives only one stream -in other words, predictable patterns should stabilize an integrated percept when compared to an arrangement of similar tones with randomly jittered feature values.…”
Section: Introductionsupporting
confidence: 55%
“…The independent manipulation of predictability was possible by systematically changing the sequential linkage between successive tones within each set ('A-A-A' and 'B-B-B') or across the sets ('A-B' and 'B-A'). Tones that are predictive of each other can be assumed to be more strongly linked in perception, and thus should be more likely to form a coherent stream [16][17][18]33]. This Manuscript submitted to Acta Acustica Bendixen et al 18 idea had been empirically demonstrated by introducing predictability separately into the 'A' and 'B' tone sets and showing that this increases stream segregation relative to an unpredictable control condition [5,30].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We suggest that this paradox can be solved by assuming that our concurrent flicker and pulse stimulation at distinct (and incommensurable) rates led to a perceptual dissociation of the visual stimulus into two distinct streams over time -a phenomenon well described as stream segregation in auditory perception (reviewed in Winkler et al 2012). …”
Section: Reversed Effect Of Synchrony On Flicker-driven Ssrsmentioning
confidence: 99%